Total phenolic and flavonoid contents of n-hexane fraction in binjai leaves (Mangifera caesia Jack. ex. Wall) - Cahaya Rahayu Yuliani; Hafiz Ramadhan; Putri Indah Sayakti; Cast Torizellia (Universitas Islam Indonesia, 2022)
AbstractBackground: Binjai leaves (Mangifera caesia Jack. ex. Wall) or M. caesia contain phenolic and flavonoid compounds important in medicinal plants development. The solvent difference and fractionation will give various active substance concentrations.Objective: To evaluate the phenolic and flavonoid content qualitatively and quantitatively from the n-hexane fraction of binjai leaves methanol extract.Methods: The soxhletation method with methanol was used to extract binjai leaves followed by fractionation. Thin Layer Chromatography (TLC) followed by spraying reagents were used to test phenols and flavonoids compounds. Folin-Ciocalteu reagents were used to analyzed total phenolics, while AlCl3 reagents were used to quantify the total flavonoid content.Result: This study gave positive results on the qualitative test of phenolics and flavonoids. Meanwhile, the fraction assay results showed total phenolic levels of 45.19 µgGAE/mg and total flavonoid levels of 165.06 µgQE/mg.Conclusion: The n-hexane fraction of M. caesia leaves methanol extracts contains phenols and flavonoid content so that it has the potential as a medicinal plant.Keywords: Binjai leaves, methanol extracts, n-hexane fraction, phenol, flavonoid. IntisariLatar belakang: Daun binjai (Mangifera caesia Jack. ex. Wall) memiliki senyawa fenolik dan flavonoid yang penting dalam pengembangan tanaman obat. Perbedaan pelarut dan fraksinasi akan memberikan kadar senyawa aktif yang berbeda.Tujuan: Penelitian ini bertujuan untuk mengetahui secara kualitatif dan kuantitatif senyawa fenolik dan flavonoid dari fraksi n-heksan ekstrak metanol daun binjai.Metode: Metode soxhletasi dengan pelarut metanol digunakan untuk mengekstraksi daun binjai yang dilanjutikan dengan fraksinasi. Kromatografi Lapis Tipis (KLT) yang dilanjutkan dengan reagen semprot digunakan untuk menguji senyawa fenolik dan flavonoid. Reagen Folin-Ciocalteu digunakan untuk menetapkan kadar total fenolik, sedangkan pereaksi AlCl3untuk menetapkan kadar total flavonoid.Hasil: Penelitian ini memberikan hasil positif pada uji kualitatif fenolik dan flavonoid, sedangkan hasil penetapan kadar fraksi memberikan hasil total fenolik sebesar 45,19 µgGAE/mg dan kadar total flavonoid 165,06 µgQE/mg.Kesimpulan: Fraksi n-heksana ekstrak metanol daun M. caesia memiliki kandungan fenolik dan flavonoid sehingga berpotensi untuk dikembangkan sebagai tanaman obat,Kata Kunci: Daun binjai, ekstrak metanol, fraksi n-heksan, fenolik, flavonoid.